2018
DOI: 10.1140/epja/i2018-12480-y
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical triton

Abstract: The symmetric components of the spatial part of S-and D-states' wavefunctions for triton ( 3 H) are investigated utilizing semiclassical expansion (in the powers of ). Analysis of the diagonalized Hamiltonian reveals the existence of two different mass states within the ground state of triton. We have solved the coupled differential equations for the two admixed states 2 S 1/2 and 4 D 1/2 owing to tensor interactions exploiting classical WKB-theory using phenomenological Feshbach-Pease potentials. The relative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…'s and hence, the disintegration energies to calculate α-decay half-lives. Being non perturbative in nature, these techniques have been employed many times in the past to understand various aspects of nuclear structure viz shell evolution [30,70,75,[88][89][90][91][92][93][94][95][96][97]. From our analysis, we have found that FRDM and our semiclassical method produce disintegration energies of same order.…”
Section: Identification Bymentioning
confidence: 79%
“…'s and hence, the disintegration energies to calculate α-decay half-lives. Being non perturbative in nature, these techniques have been employed many times in the past to understand various aspects of nuclear structure viz shell evolution [30,70,75,[88][89][90][91][92][93][94][95][96][97]. From our analysis, we have found that FRDM and our semiclassical method produce disintegration energies of same order.…”
Section: Identification Bymentioning
confidence: 79%
“…The asymptotic expansion parameter true0 [64] is small compared with the relevant classical action 1 . It is worth noting that this powerful method has been successfully used to obtain the ‘exact’ ground states for deuteron [68] and triton [69]. Moreover, we would like to recall that the semiclassical trace formula for oscillator potentials gives the exact level density, where one performs an asymptotic expansion of the energy-dependent Green function or propagator in powers of true0 [70].…”
Section: Rotating Wave Approximationmentioning
confidence: 99%
“…Semiclassical methods have been extensively used in the past to describe various physical phenomena because of their non-perturbative nature [46][47][48][49][50][51][52][53][54][55][56][57][58][59]. We have determined the α-decay half-lives of even-even SHN whose atomic numbers lie in 118 Z 126 regime employing interaction potential involving Coulomb and proximity potentials using semiclassically obtained Q α -values as an input [60].…”
Section: Introductionmentioning
confidence: 99%